2019
DOI: 10.1609/aaai.v33i01.33012093
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Enhancement via Asymmetric Signaling in Interdependent-Value Auctions

Abstract: We consider the problem of designing the information environment for revenue maximization in a sealed-bid second price auction with two bidders. Much of the prior literature has focused on signal design in settings where bidders are symmetrically informed, or on the design of optimal mechanisms under fixed information structures. We study commonand interdependent-value settings where the mechanism is fixed (a second-price auction), but the auctioneer controls the signal structure for bidders. We show that in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Our work is also related to recent literature on designing signaling schemes to influence bidders' bidding strategy (Emek et al 2012;Badanidiyuru, Bhawalkar, and Xu 2018;Li and Das 2019;Bergemann et al 2022). However, these works also focuses on the auctioneer's revenue.…”
Section: Related Workmentioning
confidence: 82%
“…Our work is also related to recent literature on designing signaling schemes to influence bidders' bidding strategy (Emek et al 2012;Badanidiyuru, Bhawalkar, and Xu 2018;Li and Das 2019;Bergemann et al 2022). However, these works also focuses on the auctioneer's revenue.…”
Section: Related Workmentioning
confidence: 82%
“…Milgrom and Weber [30] lay down the foundation and propose the well-known "Linkage Principle" that shows the expected revenue of an auctioneer can be enhanced when bidders are provided with more information about the item for a better estimate of their values. Nevertheless, it is later shown that such full transparency may not be optimal in the more general settings, no matter if the bidders are symmetrically informed or not [26,22,33]. Specifically, by careful grouping of different auction items through bundling or signaling, the optimization problem of designing the optimal revelation scheme for revenue maximization is shown to be NP-hard [19,9].…”
Section: Related Workmentioning
confidence: 99%
“…This task, also known as information design or persuasion [1,2,3,4], has attracted extensive recent interests. Besides the aforementioned problems, it has found application in many other domains including auctions [5,6,7], recommender systems [8,9,10], robot planning [11], traffic congestion control [12,13], security [14,15,16], and recently reinforcement learning [17].…”
Section: Introductionmentioning
confidence: 99%